The impact of nutritional status on centenarians’ physical, mental, and functional health - Ivan David Lozada-Martinez; Laura Vindas-Meza; Sandra Castelblanco-Toro; Juan Carlos Salazar-Uribe; Juan-Manuel Anaya (Clinical Nutrition Open Science)
Summary: Background & Aims: Nutrition has been described as a lifestyle factor strongly associated with health phenotypes in extreme longevity. However, little is known about its relationship with health-related outcomes in centenarians. Methods: A cross-sectional study was conducted from the COOLCEN cohort. The Mini Nutritional Assessment (MNA) and the Prognostic Nutritional Index (PNI) were used to determine nutritional status, which were correlated with clinical, health status, and biochemical variables. Results: The sample included 139 centenarians, 74% (n=103) were female. Centenarians at risk of malnutrition (47%; n=66) and those with an absolute PNI value < 38.8 (54%) represented the most significant proportion. MNA was positively correlated with functional independence (r2 = 0.734, P < 0.05), cognitive assessment (r2 = 0.650, P < 0.05), and functional performance (r2 = 0.619, P < 0.05). Inadequate physical performance, frailty, sarcopenia, severe dementia, some degree of dependency, low PNI, and avoiding the use of dental prosthesis were significantly associated with nutritional vulnerability (P < 0.05). Conclusions: This study identified that nutritional status in centenarians is associated with functional and cognitive status, physical performance, use of dental prostheses, and specific biochemical and anthropometric variables. These findings are relevant for decision-making in general and specialized healthcare and for public health policymakers to build evidence-based strategies to promote healthy aging.